Pelatihan Internalisasi Nilai-Nilai Karakter dalam Pembelajaran Sastra Anak Berbasis Cerita Rakyat Riau - Dwi Viora; Iis Aprinawati; Rosita; Salim (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this community service is to provide training to teachers at SDN 010 Langgini. The method of implementing this community service is carried out through a structured and practice-based training approach. From the results of observations, it can be seen that teachers are very enthusiastic in participating in the activity. Through training on internalizing character values ​​in children's literature learning based on Riau folklore, teachers become more aware of character values ​​in children's literature. Teachers also show a high level of curiosity, reflected in their enthusiasm in asking and answering questions. From this observation, it can be concluded that training on internalizing character values ​​in children's literature learning based on Riau folklore provides better benefits than just understanding children's literature. Overall, this activity has proven effective in increasing teachers' insight into the internalization of character values ​​in children's literature learning based on Riau folklore and arousing teachers' enthusiasm and curiosity because they can utilize literature in Riau.